Developing Quizizz-Based Learning Media on Digestive System Materials - Lestari, Ayu Indah; Khairuna, Khairuna (Universitas Pahlawan Tuanku Tambusai, 2022)
It requires media innovation in appropriate learning to assist students in comprehending the subject taughtÂ so that the intended learning outcomes can be achieved. It motivates schools and teachers to innovate in education relatively quickly. The study aimed to determine the responses and appropriateness of material and media experts as well as teachers and students to the Quizizz media for learning the developed Digestive System teaching materials. The study was conducted using the research and development (R&D). The participants in this study and the content used was on the Digestive System. With a score of 96%, the study concluded that the material experts to the Quizizz media in online learning of digestive system teaching materials for XI class met the very good category. The media experts indicated that the developed learning media met 94.5% for being highly usable. The percentage of teachers who responded to the used media was 94.4%, while students' responses to the use of Quizziz were very good, reaching 91.5%.Â